Memahami Dampak Media Sosial terhadap Kesehatan Mental Mahasiswa - Muthia Rahman Nayla (PT. Penerbit Tiga Mutiara, 2024)
This study aims to explore the impact of social media use on the mental health of university students. Utilizing a qualitative approach, this study analyzes data from in-depth interviews with 10 students from various universities in Indonesia. Thematic analysis reveals that social media use contributes to various aspects of mental health, including anxiety, depression, and self-image disorders. The study identifies that interactions on social media often trigger social comparison and unrealistic expectations about personal life, contributing to a decline in psychological well-being. However, the results also indicate that social media can be a useful tool for supporting mental health, particularly through support communities and awareness of mental health issues. The researchers suggest a need to increase awareness of healthy and constructive social media use among students. This study also emphasizes the importance of mental health education and intervention programs in educational institutions. These results provide insights for policymakers, educators, and mental health practitioners in developing effective strategies to support the mental health of students in the digital era. This study paves the way for further research on the specific impact of social media features and algorithms on student mental health.